Transformative learning theory, theoretical field or metatheory? - Kokkos, Alexis (Adult Education Critical Issues, 2024)
In the present response to the journal’s survey, I mainly discuss the present state of affairs of the transformative learning (TL) theoretical framework. I argue that, on the one hand, various theoretical contributions have significantly expanded and enriched Jack Mezirow’s initial conceptualization. On the other hand, the ever-increasing theoretical views led to the fragmentation of the theoretical field and to uncertainty as regards its components and terminology. Accordingly, I claim that a collective metatheoretical work that should attempt to seek for points of agreement and synthesize the various perspectives might favor the development of a more integrated TL theoretical framework.